Singapore as an ASEAN asset management hub - KOH, Francis (Institutional Knowledge at Singapore Management University, 2018)
Singapore like other ASEAN countries is also confronted with the universal challenge of retirement funding. Nonetheless, the authors argue that Singapore can address such headwind through a number of policy changes and that Singapore is uniquely placed to be the premier Asset Management Hub for the ASEAN region.